AB1194 STRIKING DIFFERENCES IN THE COURSE OF OSTEOARTHRITIS (OA) COMPARED TO RHEUMATOID ARTHRITIS (RA) OVER THE FIRST 24 MONTHS OF RHEUMATOLOGY CARE AT ONE PRIVATE PRACTICE SETTING. (13th June 2020) - Schroeder, K.; Pincus, T.; Bergman, M.
Abstract : Background: Recent reports indicate that disease burden in osteoarthritis (OA) is similar to or greater than in rheumatoid arthritis (RA) when an identical measure is used to assess patients with either disease, generally an MDHAQ/RAPID3 (multidimensional health assessment questionnaire/routine assessment of patient index data). The data suggest that a traditional view that RA is more severe than OA no longer is valid at this time. One concern is that similar disease burdens in OA vs RA may result entirely from superior treatments for RA, and RA may be considerably more severe than OA at initial presentation. Objectives: To analyze MDHAQ disease burden in patients with OA vs RA at initial visit and at 24-month follow-up in routine care at a single solo-rheumatologist private practice setting. Methods: All patients at this setting complete an MDHAQ at each visit in the waiting area, prior to seeing the rheumatologist. The MDHAQ includes three 0-10 scores for physical function, pain visual numeric scale (VNS), and patient global VNS, which may be compiled into a 0–30 RAPID3, as well as a 0-10 fatigue VNS, and 0-16 rheumatoid arthritis disease activity index (RADAI) self-report painful joint count. Mean MDHAQ scores were analyzed for all 73 OA and 116 RA patients seen for an initial visit between 2011 and 2017. Mean scores at initial and 24-month visits were compared for all 25 OA and 63 RA patients seen at 24 month (21-27 month) follow-up visits, using paired t tests. Results: Mean MDHAQ scores at first visit were similar for all 73 OA and 116 RA patients, and also for 25 OA and 63 RA patients who were also seen 24 months later, e.g., mean RAPID3 was 12.0-14.2. However, mean changes over 2 years were strikingly different in OA versus RA patients (Table). Almost all mean scores in OA were somewhat higher, while all mean scores in RA were clinically and statistically significantly improved at 24 months, e.g., mean RAPID3 worsened from 13.0 to 15.2 (+2.2 units, 17%) in OA patients, compared to improvement from 12.5 to 8.2 (-4.3 units, -34%) in RA patients. The smallest mean change in RA patients involved the joint count (7.7 to 6.1, -21%) (Table), suggesting possible control of inflammation, but continued damage to specific joints. An important limitation is that the data do not include follow-up on patients not seen over the 24 month "window, " because of substantially better or poorer status, joint surgery, or other reasons, although the data present an accurate characterization of one rheumatology practice setting. Conclusion: Mean MDHAQ/RAPID3 scores were similar in RA or OA at the initial visit. Over 24 months, scores worsened slightly in OA and improved considerably in RA, resulting in considerably poorer status in OA versus RA, likely reflecting superior treatments for RA vs OA. At an individual level, patients with primary OA may have better or poorer status than patients with primary RA. Nonetheless, at a group level, the severity of disease burden in OA appears similar to RA, and becomes greater over the next 24 months, likely as a result of better treatments. The severity of OA is underrated, suggesting a need for increased resources for research toward better treatments for OA. Disclosure of Interests: Kyle Schroeder: None declared, Theodore Pincus Shareholder of: Dr. Pincus holds a copyright and trademark on MDHAQ and RAPID3 for which he receives royalties and license fees from profit-making organizations, all of which are used to support further development of quantitative clinical measures for patients and health professionals., Martin Bergman Shareholder of: Johnson & Johnson – stockholder, Consultant of: AbbVie, BMS, Celgene Corporation, Genentech, Janssen, Merck, Novartis, Pfizer, Sanofi – consultant, Speakers bureau: AbbVie, Celgene Corporation, Novartis, Pfizer, Sanofi – speakers bureau